Behaviors related to higher education teaching developed by students of Stricto Sensu Postgraduate Behavior Analysis Programs on Brazil (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Graduate programs have two main functions: producing scientific and philosophical knowledge and training higher-level professors. This study aimed to evaluate how much the graduates of Postgraduate Programs in Behavior Analysis learned the classes of behaviors related to higher-level teaching activities. Participants were 78 graduates of master and doctoral programs from 11 Brazilian institutions, who answered an online questionnaire. It was observed that master and doctoral programs develop behaviors related to teaching practice in their students, but there are possibilities for improvement, especially in doctoral programs. The data also show that the process of learning these classes of behaviors occurs more often in the programs’ disciplines than in the teaching internships. Moreover, it indicates which classes of behavior are learned more frequently than others. It is suggested creating or improving conditions in the programs so that the behaviors acquired by students during the master's degree can be maximized in the doctorate.
Keywords: teacher training; teaching behavior analysis; stricto sensu postgraduate courses; higher level learning